If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 102 = (3x + 4)(x + -1) Reorder the terms: 102 = (4 + 3x)(x + -1) Reorder the terms: 102 = (4 + 3x)(-1 + x) Multiply (4 + 3x) * (-1 + x) 102 = (4(-1 + x) + 3x * (-1 + x)) 102 = ((-1 * 4 + x * 4) + 3x * (-1 + x)) 102 = ((-4 + 4x) + 3x * (-1 + x)) 102 = (-4 + 4x + (-1 * 3x + x * 3x)) 102 = (-4 + 4x + (-3x + 3x2)) Combine like terms: 4x + -3x = 1x 102 = (-4 + 1x + 3x2) Solving 102 = -4 + 1x + 3x2 Solving for variable 'x'. Combine like terms: 102 + 4 = 106 106 + -1x + -3x2 = -4 + 1x + 3x2 + 4 + -1x + -3x2 Reorder the terms: 106 + -1x + -3x2 = -4 + 4 + 1x + -1x + 3x2 + -3x2 Combine like terms: -4 + 4 = 0 106 + -1x + -3x2 = 0 + 1x + -1x + 3x2 + -3x2 106 + -1x + -3x2 = 1x + -1x + 3x2 + -3x2 Combine like terms: 1x + -1x = 0 106 + -1x + -3x2 = 0 + 3x2 + -3x2 106 + -1x + -3x2 = 3x2 + -3x2 Combine like terms: 3x2 + -3x2 = 0 106 + -1x + -3x2 = 0 Begin completing the square. Divide all terms by -3 the coefficient of the squared term: Divide each side by '-3'. -35.33333333 + 0.3333333333x + x2 = 0 Move the constant term to the right: Add '35.33333333' to each side of the equation. -35.33333333 + 0.3333333333x + 35.33333333 + x2 = 0 + 35.33333333 Reorder the terms: -35.33333333 + 35.33333333 + 0.3333333333x + x2 = 0 + 35.33333333 Combine like terms: -35.33333333 + 35.33333333 = 0.00000000 0.00000000 + 0.3333333333x + x2 = 0 + 35.33333333 0.3333333333x + x2 = 0 + 35.33333333 Combine like terms: 0 + 35.33333333 = 35.33333333 0.3333333333x + x2 = 35.33333333 The x term is 0.3333333333x. Take half its coefficient (0.1666666667). Square it (0.02777777779) and add it to both sides. Add '0.02777777779' to each side of the equation. 0.3333333333x + 0.02777777779 + x2 = 35.33333333 + 0.02777777779 Reorder the terms: 0.02777777779 + 0.3333333333x + x2 = 35.33333333 + 0.02777777779 Combine like terms: 35.33333333 + 0.02777777779 = 35.36111110779 0.02777777779 + 0.3333333333x + x2 = 35.36111110779 Factor a perfect square on the left side: (x + 0.1666666667)(x + 0.1666666667) = 35.36111110779 Calculate the square root of the right side: 5.946520925 Break this problem into two subproblems by setting (x + 0.1666666667) equal to 5.946520925 and -5.946520925.Subproblem 1
x + 0.1666666667 = 5.946520925 Simplifying x + 0.1666666667 = 5.946520925 Reorder the terms: 0.1666666667 + x = 5.946520925 Solving 0.1666666667 + x = 5.946520925 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.1666666667' to each side of the equation. 0.1666666667 + -0.1666666667 + x = 5.946520925 + -0.1666666667 Combine like terms: 0.1666666667 + -0.1666666667 = 0.0000000000 0.0000000000 + x = 5.946520925 + -0.1666666667 x = 5.946520925 + -0.1666666667 Combine like terms: 5.946520925 + -0.1666666667 = 5.7798542583 x = 5.7798542583 Simplifying x = 5.7798542583Subproblem 2
x + 0.1666666667 = -5.946520925 Simplifying x + 0.1666666667 = -5.946520925 Reorder the terms: 0.1666666667 + x = -5.946520925 Solving 0.1666666667 + x = -5.946520925 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.1666666667' to each side of the equation. 0.1666666667 + -0.1666666667 + x = -5.946520925 + -0.1666666667 Combine like terms: 0.1666666667 + -0.1666666667 = 0.0000000000 0.0000000000 + x = -5.946520925 + -0.1666666667 x = -5.946520925 + -0.1666666667 Combine like terms: -5.946520925 + -0.1666666667 = -6.1131875917 x = -6.1131875917 Simplifying x = -6.1131875917Solution
The solution to the problem is based on the solutions from the subproblems. x = {5.7798542583, -6.1131875917}
| h(t)=-16t^2+65t+6 | | 4z^2+30=24z | | 2x-3/6=8-x/4 | | 12b+16=8(-5b-11) | | X-1/2=1/6x | | 200+20t^3= | | X-18=-2.6 | | 1.5+15=2.25 | | 8/12=9 | | 0.5(4d-2)=2+2d | | 7+18=18+7 | | 10x+40=-4x+12 | | 2(6-3x)+x= | | A(x)=-x^2+90x | | 6(4.3+2.2x)=4x-5.9+7.2x | | -8=X11/2 | | 4(8-y)=2(3y+2)+8 | | Sin^2x-4cosx-11=0 | | 36x^4+4x^2+9=0 | | 8-3=2 | | 8.3x+-3.1=-37.35 | | 4.6x+2.3=-18.36 | | 36x^2+4x^2+9=0 | | 2(2b-5)=4(b-2) | | (m+9)(m-8)=0 | | 34=2x+(4+.5x) | | 6/c=-4 | | 7(21x/3y)=7 | | X=(3x+7)(3x+7) | | -2(a+15)=7+3a-37-5a | | 11-x=1/2(x-13)squared | | 1+x^4=0.12 |